Economic value of water in the Alfajayucan (100) district of irrigation, Hidalgo - Martínez-Luna, Domingo; Mora-Flores , José S.; Exebio-García, Adolfo A.; Arana-Coronado, Oscar A.; Arjona-Suárez, Enrique (REVISTA TERRA LATINOAMERICANA, 2021)
Water for human consumption is supplied for different demanded uses: domestic, agriculture and industry. According to what has been reported by FAO and UNESCO, agriculture consumes 69% of water; domestic purposes consume 10% and industry 21%. Given the importance of water in agriculture and crop pattern, knowledge on the optimal allocation and economic value of the resource is required. The objective of our study was to obtain an optimal crop pattern in the Irrigation District 100 (ID 100) Alfajayucan Hidalgo, as well as to estimate the economical price of water under different scenarios. The hypothesis states that the fees paid by farmers in ID 100 do not reflect their true scarcity value. A linear programming model was implemented to maximize the net income of farmers with 17 cyclical and perennial agricultural activities, subject to 57 surface restrictions, water, labor and machinery. The results indicate that the net income of ID 100 would increase by 273 million if the optimal crop pattern is established, compared to that obtained in the 2015‑2016 agricultural cycle. The economical price of the water according to the model was 1.44 m-3, much higher than that currently paid (irrigation fees = 0.02 m-3), conf irming the existence of a strong subsidy to the water supply. Thus, in light our results, the water fees paid by farmers should increase.